Evaluation of Mineral (Na, K, Ca) and Metal (Fe, Cu, Ni) Content, Alongside Phytochemical Screening of Eriobotrya japonica L. Grown in Two Different Locations in Libya - Ahlam Alaila; Rabha Bouhuish; Rania Ali; Hanadi Al Naji; Hamad Hasan; Zuhir Akrim (AlQalam Journal of Medical and Applied Sciences, 2025)
The current study was carried out on the (Eriobotrya japonica L.) plant grown at two different locations in Libya. The samples of the studied plant were collected from some regions around Al Gabal Alkhder and coastal locations. The leaves and fruits were selected. The phytochemical screening and concentrations of some metals (Iron, Copper, and Nickel) and minerals (Sodium, Potassium, and Calcium). The phytochemical investigation was conducted on the samples to detect the natural compounds, and the atomic absorption instrument was used to measure the concentrations of heavy metals (Fe, Cu, and Ni). On the other side, the contents of minerals (Na, K, and Ca) were estimated by a Flame photometer. The results of this study recorded the results of the general phytochemical screening of all parts of the plant. Phytochemical screening of the aqueous and ethanol extracts shows the presence of the natural compounds as tannins, flavonoids, sterols, and/or triterpenes, saponins, alkaloids, anthraquinone, and compounds were present in the extracts with varying amounts. In the present study, results showed that E. japonica plant contains different phytochemical compounds such as Sterols and Saponins. For the Tannins compound, the results showed that the samples leaf contained high levels of tannins in water extracts, high levels of extract ethanol, and the fruitse extract of ethanol containing high contents of compound tannins compared to water extracts. The minerals and metal contents of the studied plants gave variations where the sodium, potassium, and calcium were (2.51 -3.55 ppm) in leaves and (3.76- 4.74 ppm) in fruits. While the concentrations of potassium ranged (26.46 -40.46 ppm) in leaves and (8.50 -31.46 ppm) in fruits. On the other side, the concentrations of calcium fluctuated between (0.26- 0.62 ppm) in leaves and in fruits ranged (7.84-10.45 ppm). The results indicated that the higher concentrations of minerals were recorded in the mountain regions, such as around Al Quba city and Ain Marra town. On the other side, the contents of iron ranged between (0.084 – 2.85 ppm) and (0.49-7.89 ppm) in leaves and fruits, respectively. While the contents of Nickle were ranged between (1.08-2.02 ppm) and (1.32- 7.34 ppm). The concentrations of copper were ranged as follows (2.50-8.46 ppm) and (64.38 – 75.62 ppm) in leaves and fruits. The study stated that there are variations in the minerals and metals contents, with the higher values being recorded in mountain location samples compared with the coastal plant samples. ns in the minerals and metals contents, the higher values were recorded in the mountain location samples compared with the coastal plant samples.